Uji Sitotoksisitas Ekstrak Etanol Herba Ceplukan (Physalis angulata Linn.) terhadap Sel T47D secara In Vitro - IRA DJAJANEGARA; PRIYO WAHYUDI (Fakultas Farmasi Universitas Pancasila, 2010)
Cutleaf groundcheny (Physalis angulata Linn.) is a popular traditional medicine. This experiment was conducted to investigate the possible role of the herbal extract as an anticancer agent using T47D breast cancer cell line. Cytotoxicity assay was caried out by direct counting method. Breastcancer T47D cell lines Were treated with 70% ethanol extract from cutleaf groundcherry fruit with serial dilution of 2000, 1000, 500, 250, 125, 62.5, and 31.25 µg/ml for 24 hours of incubation at 37°C As a positive control doxorubicin was also tested on the breast cancer T47D cell lines with serial dilution of 20, 10, 5, 2.5, 1.25, 0.625, 0.312, and 0.156 µg/ml for 24 hours of incubation at 37°C The amount of living cells were observed and counted, death percentage was then determined and probit analysis was used to determine the LC50 value. The LC50 value for ethanol extract from the fruits was 28,02 µg/ml While doxorubicin as the positive control was 0,113 µg/ml. It is concluded that the cutleaf groundcherry (Physalis angulata) fruits have a cytotoxic activity toward T47D (breast cancer) cell lines which confirmed previous toxicity experiment using brine shrimp lethality test (BSLT) method.